Biology of the people of Tamil Nadu - Sanghvi, L. D.; Balakrishnan, V.; Karve, Irawati Karmarkar, 1905-1970 (Indian Society of Human Genetics ; Indian Anthropological Society, 1981)
Contributed articles on the population structure and genetic variation in Tamil Nadu.